Iridium‐Catalyzed Reductive Nitro‐Mannich Cyclization. Issue 1 (14th November 2014) - Gregory, Alex W.; Chambers, Alan; Hawkins, Alison; Jakubec, Pavol; Dixon, Darren J.
Abstract A new chemoselective reductive nitro‐Mannich cyclization reaction sequence of nitroalkyl‐tethered lactams has been developed. Relying on the rapid and chemoselective iridium(I)‐catalyzed reduction of lactams to the corresponding enamine, subsequent nitro‐Mannich cyclization of tethered nitroalkyl functionality provides direct access to important alkaloid natural‐product‐like structures in yields up to 81 % and in diastereoselectivities that are typically good to excellent. An in‐depth understanding of the reaction mechanism has been gained through NMR studies and characterization of reaction intermediates. The new methodology has been applied to the total synthesis of (±)‐epi‐epiquinamide in four steps.